2014
DOI: 10.1016/j.jcm.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Treatment Program Comparing 2 Different Traction Approaches for Patients With Discogenic Cervical Radiculopathy: A Randomized Controlled Trial

Abstract: Objective: The purpose of this study was to investigate the immediate and long-term effects of a 1-year multimodal program with the addition of 2 different traction approaches on the pain, function, disability, and nerve root function in patients with discogenic cervical radiculopathy (CR). This study also attempted to identify the optimal traction angle based on the maximum recovery of the peak-to-peak amplitude of the flexor carpi radialis (FCR) H-reflex. Methods: This randomized clinical trial with one-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 50 publications
1
47
0
1
Order By: Relevance
“…This increased tension provides resistance against the necessary shortening and swelling of nerve fibers that accompany an action potential. This tension can give rise to local and distant signs and symptoms including neuralgias, spasticity, dizziness, bladder dysfunction, cervical and lumbar spondylosis, disk hernias, trauma to the spinal cord, and autoimmune disorders [23][24][25][26]32,33,47]. This serves as a proposed mechanism for the source of this patient's health conditions due to their resolution following sagittal cervical spinal correction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increased tension provides resistance against the necessary shortening and swelling of nerve fibers that accompany an action potential. This tension can give rise to local and distant signs and symptoms including neuralgias, spasticity, dizziness, bladder dysfunction, cervical and lumbar spondylosis, disk hernias, trauma to the spinal cord, and autoimmune disorders [23][24][25][26]32,33,47]. This serves as a proposed mechanism for the source of this patient's health conditions due to their resolution following sagittal cervical spinal correction.…”
Section: Discussionmentioning
confidence: 99%
“…Chiropractic BioPhysics® (CBP®) technique is a full-spine and posture rehabilitation approach to correcting poor posture, deviation of normal spinal alignment and subluxation through incorporating mirror image® exercise, adjustments, and traction procedures [27][28][29][30][31]. CBP® has an extensive amount of quality scientific evidence supporting reliable correction of spinal and postural misalignment yielding improvements in concomitant neurological, musculoskeletal symptoms, spine movement, and patient disability levels [20,[23][24][25][26]32,33]. It seems logical to propose that improvements in spinal and neurological health may have a beneficial impact on TL.…”
Section: Page 2 Ofmentioning
confidence: 99%
“…Of note, the improvements in PROs reported in this study were achieved in a pilot RCT that was only two weeks in duration. Future RCTs that evaluate MCD might extend the course of care to four or six weeks, as is delivered in clinical practice [ 34 ] and in recent clinical trials of traction-based therapies which demonstrated both short-term and longer term improvements in neck pain intensity and disability following four weeks of treatment [ 24 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Each patient had strengthening exercises of deep neck flexors through tucking the chin in from supine lying position with the head in contact with the plinth without any pillow [29]. This exercise was frequently performed for 3 sets of 10 repetitions and the holding time of exercise was 5 or 6 s.…”
Section: Strengthening Exercises For Deep Neck Flexorsmentioning
confidence: 99%